Urbanization as a Tipping Point: Threshold Effects on Carbon Emissions in EU Countries - Chovancová, Jana; Petruška, Igor (European Journal of Sustainable Development, 2025)
This study explores how the impact of structural drivers on CO? emissions varies at different levels of urbanisation in EU countries, reflecting the broader implications for sustainable economic development. To this end, we apply a threshold panel regression model. Using urbanisation as the threshold variable, the model identifies a statistically significant threshold of 92.572% urban share, dividing the sample into less and highly urbanised countries. The results show that the effect of energy use on emissions is significant in less urbanised areas, but becomes insignificant above the threshold. This suggests that energy efficiency and decarbonisation are enhanced in more urbanised settings. Renewable energy consistently reduces emissions in both regimes, with a notably stronger effect in highly urbanised areas. Land use and forestry (LULUCF) only exhibit a mitigating effect in less urbanised countries. Interestingly, the effect of urbanisation itself is nonlinear: while moderate urbanisation reduces emissions, further urban growth beyond the threshold increases them, likely due to infrastructure saturation and lifestyle changes. These findings provide empirical evidence of a tipping point in the urbanisation-emissions relationship and emphasise the need for decarbonisation strategies that are tailored to the level of urbanisation and aligned with long-term sustainability goals. Keywords: Urbanization, CO? emissions, Threshold regression, Bootstraping, Renewable energy, LULUCF, Energy use, EU countries